APPLICATION OF MULTI-SCALE BASE IN THE SPHERE OF LAND MANAGEMENT (Proceedings of the YSU C: Geological and Geographical Sciences, 2017)
In this article the problem of providing to organs of executing control of land resources with complex data (including the appropriate maps and databases) about land resources has been studied. Today it is impossible to solve this problem without appropriate software, geoinformation system and multi-scale maps, which form basis for them. Each government proceeding from its territory and features determine succeeding scales of base maps. These maps, which are created in uniform coordinate and high-rise systems, are intended for solving different tasks arising before the country. In corresponding software package the usage of topographic and cadastral maps together with remote sensing will allow to derive multi-scale base map consisting of several large-scale theme groups and layers.
Keywords: effective land use; land management; multi-scale cartography; succeeding scales; cadastral registry; geoinformation systems